Do benefício assistencial de prestação continuada e a alteração trazida pelo parágrafo único do artigo 34 do Estatuto do Idoso (Lei N. 10.742/03) - Cavassana, Maruza Rubia (2010)
With the Brazilian Constitution of 1988, the Social Care in Brazil, as a part of Social Security, is allied to guarantee human dignity and transcends the idea of charity and benevolence established before, now its is explicitly recognized as a fundamental right (articles 6 and 230 of Brazilian Constitution). The Assistance Benefit of Continued Service to the handicapped and the elderly is today the main provision of Social Security of our law system. With the "Elderliness Statute" (law number 10,742/2003) the necessary requirements for granting the Assistance Benefit of Continued Service to the Elderly have changed, which means: to reduce the age of 67 years to 65 years, and the exclusion of income from other Assistance Benefit of Continued Service to the elderly from computation on a quarter of the minimum wage per capita, which is used as a criterion for measuring poverty. This last amendment relaxes the requirement and brings with it questions about the constitutionality of the law (article 34 of law number 10,742/2003) when it is analyzed under constitutional principles such as: the value of human dignity, equality, isonomy, the prohibition of social retrocession, and their relationship with the possibilities of reality. With regard to theoretical and methodological issues, there were done studies of articles, doctrines, jurisprudence, laws, and the Constitution when related to the topic examined